Entre ville et campagne, le difficile équilibre des périurbaines lointaines - Nathalie Ortar (Métropoles)
Suburbs attract bi-actives households with young children. Those couples are settled farther and farther in the countryside. The investigation brought to light the need to study women’s situation the situation because of the reported difficulties to remain in employment. This article is therefore about women’s work situation, as well as work/life balance.